The Financial System in the Czech Republic, Hungary and Poland after a Decade of Transition - Franz Schardax; Thomas Reininger; Martin Summer (Deutsche Bundesbank, 2001)
The Czech Republic, Hungary and Poland (CEEC-3) have undertaken substantial efforts to build a new financial system under the constraints of their legacies from central planning. In this study, first we look at the banking sector. Then we give a description of bond and stock markets. These topics are complemented by an analysis of the structure of funding for the private and public sector, of the financial sector's vulnerability and of the legal conditions for external finance as well as for banking supervision. We find that the financial sector and financial intermediation are internationally integrated already to a large extent. This implies, inter alia, a non-negligible exposure of the corporate sector to exchange rate risk. While funding via equity markets remained modest, local currencydenominated debt issues are important for public financing. Our analysis shows that the legal, supervisory and regulatory infrastructure of the financial system is formally well developed, but suffers from enforcement problems. – – Polen, die Tschechische Republik und Ungarn unternahmen, ausgehend vom Erbe der zentralen Planwirtschaft, substanzielle Anstrengungen zur Errichtung neuer Finanzsysteme. Aufbauend auf einer Untersuchung des Bankensektors sowie der Kapitalmärkte erfolgt eine Analyse der Finanzierungsstruktur des privaten und des öffentlichen Sektors, der Krisenanfälligkeit des Finanzsektors sowie der rechtlichen Regelungen für externe Unternehmensfinanzierung und Bankenaufsicht. Finanzsektoren und -intermediation sind bereits in hohem Maße international integriert. Dies impliziert u.a., dass der Unternehmenssektor einem beachtlichen Wechselkursrisiko ausgesetzt ist. Während die Finanzierung über den Aktienmarkt gering ist, sind in nationaler Währung denominierte Schuldtitel für die Finanzierung des öffentlichen Sektors wichtig. Unsere Analyse zeigt, dass der rechtliche und aufsichtsrechtliche Rahmen der Finanzsysteme formal gut entwickelt ist. Es gibt jedoch Mängel bei der praktischen Umsetzung dieser Standards.
Keywords: G00; O16; O57; P52; 330; Financial System in Czech Republic; Hungary and Poland; Financial Sector Transition; Transition Economics; Finanzsektor; Bankensystem; Übergangswirtschaft; Finanzierung; Tschechische Republik; Ungarn; Polen